PECULIARITIES OF DIAGNOSTICS AND TREATMENT OF RHEUMATOID ARTHRITIS AT EARLY STAGES OF ITS DEVELOPMENT (World Bulletin of Public Health, 2024)
The review summarises current advances in the study of early diagnosis and treatment of rheumatoid arthritis (RA). The evolution of RA includes several consecutive (or discrete) stages of development, culminating in the development of a complex of symptoms characteristic of RA. However, the nature of the interaction between environmental factors, genetic predisposition, and immune mechanisms that determine stage-to-stage transition and developmental variants is not entirely clear and is currently the subject of intensive research. The article lists modern classification criteria of RA (ACR/EULAR, 2010), created for early diagnosis of the disease. Emphasis is placed on the use of methotrexate (MT) as the "gold standard" of RA pharmacotherapy and a key component of the "Treat to Achieve" strategy. Early administration of MT (including in subcutaneous form) should be a mandatory component of RA treatment at all stages of the disease. When using MT as monotherapy or in combination with baseline anti-inflammatory drugs (BIDs), if remission is not achieved, then genetically engineered biological drugs (GEBPs) should be prescribed
Keywords: Rheumatoid arthritis; rheumatoid factor; antibodies to cyclic citrullinated peptides